Alterations in ventricular KATP channel properties during aging. Issue 1 (17th December 2012) - Bao, Li; Taskin, Eylem; Foster, Monique; Ray, Beevash; Rosario, Rosa; Ananthakrishnan, Radha; Howlett, Susan E.; Schmidt, Ann M.; Ramasamy, Ravichandran; Coetzee, William A.
Summary Coronary heart disease remains the principle cause of mortality in the United States. During aging, the efficiency of the cardiovascular system is decreased and the aged heart is less tolerant to ischemic injury. ATP‐sensitive K+ (KATP) channels protect the myocardium against ischemic damage. We investigated how aging affects cardiac KATP channels in the Fischer 344 rat model. Expression of KATP channel subunit mRNA and protein levels was unchanged in hearts from 26‐month‐old vs. 4‐month‐old rats. Interestingly, the mRNA expression of several other ion channels (> 80) was also largely unchanged, suggesting that posttranscriptional regulatory mechanisms occur during aging. The whole‐cell KATP channel current density was strongly diminished in ventricular myocytes from aged male rat hearts (also observed in aged C57BL/6 mouse myocytes). Experiments with isolated patches (inside‐out configuration) demonstrated that the KATP channel unitary conductance was unchanged, but that the inhibitory effect of cytosolic ATP on channel activity was enhanced in the aged heart. The mean patch current was diminished, consistent with the whole‐cell data. We incorporated these findings into an empirical model of the KATP channel and numerically simulated the effects of decreased cytosolic ATP levels on the human action potential. This analysis predicts lesser activation of KATP channels by metabolic impairment in the aged heart and a diminished action potential shortening. This study provides insights into the changes in KATP channels during aging and suggests that the protective role of these channels during ischemia is significantly compromised in the aged individual.